Electrochemical synthesis of novel conductive polymer and corrosion protection properties on aluminium. (November 2013) - Mert, B. D.; Yazıcı, B.; Lyon, S. B.
Abstract : In this study, the new original copolymer film of pyrrole and 2-amino-4-methyl-pyridine has been electrochemically synthesised on 7075 aluminium alloy. The synthesis was achieved in aqueous oxalic acid containing 1∶1 monomer feed ratio. The characteristics of copolymer film were compared with polypyrrole film on Al under the same conditions. The characterisation of synthesised polymers was realised with the help of scanning electron microscopy. Fourier transform infrared spectroscopy and gel permeation chromatography techniques. The conductivity values of films were measured with four-probe technique. The stability of copolymer film as a coating material has also been investigated in 3·5% NaCl solution. The quantum theoretical calculations have been employed, and some parameters (dipole moment, energy of the highest occupied molecular orbital and lowest unoccupied molecular orbital) were determined. The calculated quantum parameters revealed correlation with experimental data. Under such severe conditions, the copolymer film exhibits protective coating behaviour on Al. This original, highly stable and conductive copolymer film can find wide application area for various purposes (anticorrosive, electrocatalytic, etc.).